Reducing Burnout at MI Nurul Mun’im: The Role of Emlpoyee Resilience in Human Resource Management - Tsamar Nur Aini; Misbahul Arifin; Deni Wahyuni; Ummul Khoiroh (AL-BAYAN INSTITUTE, 2025)
This study focuses on strategies for enhancing teacher resilience to prevent burnout at MI Nurul Mun’im, aiming to explore the roles of leadership, work-life balance, and social support in building individual and collective fortitude within the work environment. Utilizing a qualitative approach with a case study design, data were collected through observation, in-depth interviews with the headmaster, vice headmaster, teachers, and students, as well as document analysis. Data analysis involved reduction, display, and verification using content, discourse, and interpretive analysis methods. The findings indicate that participatory and appreciative leadership strategies significantly increase teachers' sense of ownership and motivation, while work-life balance policies, such as flexible scheduling and reduced administrative burdens, support their physical and mental well-being. Furthermore, social support, fostered through harmonious relationships among teachers and group discussion programs, strengthens collective resilience, positively impacting both the work and learning atmosphere. The implications of this research suggest that the combination of these strategies can serve as an effective model for improving educator well-being and, ultimately, the quality of education